The Announcement Effects of Insider Trading - Ahmad Fawwaz, Mohd Nasarudin (2009)
This paper examines the insider trading activity in Malaysia. It tries to examine the existence of the abnormal profit from this activity. While developed countries like United States and United Kingdom recently reported that the activity can no longer gives abnormal profit for long period due to laws imposed in those countries, attention now turns to emerging market like Malaysia. By using event study analysis, 200 cases of insider trading activity reported between January 2008 and March 2009 were closely examine and the result shows that while abnormal return do exist, it is mostly not significant. This paper also looks at the individuals and institutional insider and their performances respectively.